Evaluation of Crude Fat, Crude Fiber, and Gross Energy Content of Palm Kernel Meal Fermented with EM-4 (Effective Microorganisms-4) at Different Fermentation Durations - Putra, Randi Eka; Surtina, Dara; Harissatria, Harissatria (Journal of Animal Nutrition and Production Science, 2024)
This research aims to determine the effect of fermentation time for palm kernel meal using EM-4 (Effective Microorganism-4) on the crude fat, crude fiber, and gross energy contents. This is clear, but you might add a location like "in Padang, Indonesia" for an international audience. The treatments were as follows: P0 (no fermentation), P1 (fermentation for 7 days), P2 (fermentation for 14 days), and P3 (fermentation for 21 days). The parameters measured included the crude fat, crude fiber, and gross energy contents. Based on the results, it can be concluded that the fermentation time of palm kernel meal using EM-4 significantly affects (P<0.01) the crude fiber content but does not significantly affect (P>0.05) the crude fat content or the gross energy of the palm kernel cake palm kernel.